JOB ANALYSIS APPROACH IN IMPROVING HR MANAGEMENT EFFECTIVENESS AT PT INDOFOOD SUKSES MAKMUR TBK - Dira Nurhikmah; Hendra Riofita (LPPM Politeknik Pratama, 2024)
This research aims to analyze the job analysis approach in improving the effectiveness of human resource management (HRM) at PT Indofood Sukses Makmur Tbk. In the era of globalization and increasing business competition, companies are required to have an efficient and adaptive HRM system. Job analysis serves as a crucial component that systematically designs, manages, and evaluates work according to organizational needs. The research method used in this study is a literature review by examining various sources such as journals, books, and e-books related to HRM and job analysis. The results indicate that the implementation of job analysis at PT Indofood Sukses Makmur Tbk significantly enhances HRM effectiveness, particularly in recruitment, training, performance appraisal, and compensation systems. Through job analysis, the company can ensure alignment between individual competencies and job requirements, improve productivity, and create an objective and transparent performance evaluation system. Moreover, job analysis plays an essential role in preventing overlapping tasks and improving coordination among departments. The study concludes that job analysis is not merely an administrative activity but a strategic instrument for developing an effective, efficient, and sustainable HRM system.